Determinants of FDI from Visegrad countries in China and India: Long-term and short-term perspectives - Geise, Andrzej; Jaworek, Małgorzata; Kuczmarska, Magdalena (Bulletin of Geography. Socio-economic Series, 2025)
This article examines the determinants of foreign direct investment (FDI) undertaken in China and India by companies from the Visegrad Group (Poland, the Czech Republic, Slovakia, and Hungary). We examine the impact of several host country factors (like on the FDI using the panel autoregressive distributed lag (p-ARDL) model to assess the short- and long-term connectedness. Econometric models were constructed using time-series stacks from 2006-2021. The main research results suggest that GDP per capita (representing market-related determinants) and trade openness (representing policy framework determinants) significantly and positively influence FDI outward stocks from the Visegrad Group into China and India in the long term. The remaining determinants considered in the study, such as labour costs (efficiency determinant), inflation (policy framework), and R&D expenditures (strategic assets determinants), were statistically insignificant factors in the long term. However, those factors play an essential role as short-run determinants, where the relationship running from labour costs, trade openness and R&D expenditures to FDI suggests that those determinants can increase the FDI of the Visegrad Group countries in the short term.